Corellation Between Education and Football Club's Performance - Jayawardhana, Irman (Prasetiya Mulya Publishing, 2023)
Performance management is the tools for a sport organisation to measure their success. Previous studies have argued that a country’s success in sports is influenced by socio-economic factors that happen in that country. However, the factors that are used to determine the levels of success for football clubs are not necessarily the same, or bear the same weight. This study analyzes the influence of education in football clubs’ performance. The novelty of this work is that football clubs is treated as a business company that using measured performance indicator, cost efficiency and education as variables and determinants. Using an empirical analysis, the presented idea is to identify specific factors that raise football club’s success by means of several econometric specifications using panel data for European football clubs which playing in UEFA’s competition. It is found an evidence that education and football club’s expenditure caused to the sport performance. However, the club’s performance would be declining if it is influenced by certain part of education factor.